LITERATURE STUDY ON ELEMENTARY ETHNOMATHEMATICS FOR MATHEMATICAL LITERACY - Wahyuni, Eka; Suherman, Suherman; Ismaya, Ismaya (Universitas Muhammadiyah Enrekang, 2023)
This scientific work aims to collect literature related to ethnomathematics models in elementary schools to provide mathematical literacy which is expected to be a learning reference for educators/teachers and students in improving students' mathematics learning outcomes which are managed from various kinds of information, such as: books, journals, articles, other scientific works. In this study, 5 (five) published journals were taken so that the data or theory presented was sufficiently strong and clear. The method used in this scientific work is library research where library research is used to collect various data sources or theories that support the formation of this scientific work.